Opozycja swój / obcy w zapiskach Marii Pawlikowskiej-Jasnorzewskiej z lat 1939–1945 - Wojciechowska, Anna (Stylistyka, 2019)
The aim of this paper is to present the US–THEM opposition (which is important in the study of the linguistic image of the world) in a particular autobiographical statement, that is, in the notes of Maria Pawlikowska-Jasnorzewska written during the years 1939–1945. After the reconstruction of the image of her family, countrymen, and foreigners captured in the text, one may conclude that the boundaries between the US–THEM categories seem to blur. Thus, the US–THEM status is not constant. It is important to emphasise that the choice of specific markers of foreignness and closeness is strictly related to the author’s value-system. It can be seen from the data that the US comprises a small circle of people, to whom she is bound, and who share similar ways of perceiving the world, and who give her a sense of security. The THEM, on the other hand, are those people with whom the poet is unable to communicate – in the literal and metaphorical sense. The analysis also allow to see the influence of external conditions on the author’s various style choices. The text is strongly marked by subjectivity and reveals emotional and evaluative attitude of the speaking subject towards the reality presented. It is due to the use of such stylistic devices as: emotionally coloured lexicon, metaphors containing evaluating elements, code-switching, interjections, etc.